MicroRNAs Are Mediators of Androgen Action in Prostate and Muscle - Narayanan, Ramesh (Public Library of Science, 2010)
Androgen receptor (AR) function is critical for the development of male reproductive organs, muscle, bone and other tissues. Functionally impaired AR results in androgen insensitivity syndrome (AIS). The interaction between AR and microRNA (miR) signaling pathways was examined to understand the role of miRs in AR function. Reduction of androgen levels in Sprague-Dawley rats by castration inhibited the expression of a large set of miRs in prostate and muscle, which was reversed by treatment of castrated rats with 3 mg/day dihydrotestosterone (DHT) or selective androgen receptor modulators. Knockout of the miR processing enzyme, DICER, in LNCaP prostate cancer cells or tissue specifically in mice inhibited AR function leading to AIS. Since the only function of miRs is to bind to 3′ UTR and inhibit translation of target genes, androgens might induce miRs to inhibit repressors of AR function. In concordance, knock-down of DICER in LNCaP cells and in tissues in mice induced the expression of corepressors, NCoR and SMRT. These studies demonstrate a feedback loop between miRs, corepressors and AR and the imperative role of miRs in AR function in non-cancerous androgen-responsive tissues.